Recent Advances of Energy Solutions for Implantable Bioelectronics. Issue 17 (30th April 2021) - Sheng, Hongwei; Zhang, Xuetao; Liang, Jie; Shao, Mingjiao; Xie, Erqing; Yu, Cunjiang; Lan, Wei
Abstract: The emerging field of implantable bioelectronics has attracted widespread attention in modern society because it can improve treatment outcomes, reduce healthcare costs, and lead to an improvement in the quality of life. However, their continuous operation is often limited by conventional bulky and rigid batteries with a limited lifespan, which must be surgically removed after completing their missions and/or replaced after being exhausted. Herein, this paper gives a comprehensive review of recent advances in nonconventional energy solutions for implantable bioelectronics, emphasizing the miniaturized, flexible, biocompatible, and biodegradable power devices. According to their source of energy, the promising alternative energy solutions are sorted into three main categories, including energy storage devices (batteries and supercapacitors), internal energy‐harvesting devices (including biofuel cells, piezoelectric/triboelectric energy harvesters, thermoelectric and biopotential power generators), and external wireless power transmission technologies (including inductive coupling/radiofrequency, ultrasound‐induced, and photovoltaic devices). Their fundamentals, materials strategies, structural design, output performances, animal experiments, and typical biomedical applications are also discussed. It is expected to offer complementary power sources to extend the battery lifetime of bioelectronics while acting as an independent power supply. Thereafter, the existing challenges and perspectives associated with these powering devices are also outlined, with a focus on implantable bioelectronics. Abstract : The energy supply of implantable bioelectronics usually depends on bulky and rigid batteries, which have to be surgically removed or replaced periodically owing to their limited capacity. Based on this, various promising alternative energy solutions are classified and reviewed, which can not only provide complementary powering devices to extend the battery lifetime but also serve as independent power supplies.